Thomas J. Catlaw, Fabricating The People: Politics and Administration in The Biopolitical State - Antonius Galih Prasetyo (Magister Ilmu Administrasi Publik, 2012)
Book Review (Alamaba: The University of Alamaba Press, 2007, 258 hal)